Hidróxidos duplos lamelares magnéticos: adsorção de cobalto(ii) e aplicação do material saturado como catalisador na degradação de nitroarenos - Fernandes, Jardel Lopes (2025)
Herein, iron oxide nanoparticles coated with nickel–iron layered double hydroxides (Mag-LDH-NiFe) were prepared and characterized using the coprecipitation method. The magnetic LDH was employed as an adsorbent for cobalt ions (Co2+) in aqueous solution, and the resulting material was applied as a catalyst in the catalytic reduction of nitroaromatic compounds. The obtained LDHs were characterized by powder X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) coupled with energy-dispersive X-ray spectroscopy (EDS), transmission electron microscopy (TEM), surface area and porosity analysis (BET), and flame atomic absorption spectrometry (FAAS). The point of zero charge (pHPZC) of Mag-LDH-NiFe was also determined, assessing the dependence of the solid surface charge on the solution pH, an important factor in the adsorption of cobalt cations. Adsorption experiments showed efficient removal of cobalt ions from aqueous media, and the Langmuir isotherm fitting indicated a maximum adsorption capacity of approximately 15.95 mg g-1 for Mag-LDH-NiFe. The solid used as a catalyst after cobalt adsorption proved to be efficient in the catalytic reduction of 4-nitrophenol, enhancing the apparent rate constant (kapp) of the reaction by nearly nine times compared to the cobalt-free material. The reaction followed the Langmuir–Hinshelwood model. The catalyst was reused for ten consecutive cycles, maintaining 100% substrate conversion, despite a gradual decrease in the reaction rate. Furthermore, the cobalt-modified catalyst demonstrated versatility in reducing other nitroarenes, such as 4-nitrotoluene, 2,4-dinitrophenol, and 1-chloro-4-nitrobenzene, regardless of the presence of electron-donating or electron-withdrawing substituents. These results highlight the material's potential for practical and sustainable applications, offering high catalytic efficiency, structural stability, and recyclability.